Vida Activa para una Buena Salud: Personas de la Tercera Edad - Jennifer Hillan; Anne Kendall (EDIS)
FCS-8753-Span, a 2-page fact sheet by Jennifer Hillan and Anne Kendall, is the Spanish version of "Living Actively for Good Health: Older Adults" (FCS8753). It encourages older adults to engage in regular physical activity, listing the advantages of this practice and suggesting ways to overcome possible barriers and stay safe. Published by the UF Department of Family, Youth and Community Sciences, June 2007.